India needs agroforestry policy urgently: Issues and challenges - Dhyani, S.K.; Handa, A.K. (Indian Journal of Agroforestry, 2020)
Agroforestry is emerging as a major land use activity in the country after agriculture and forestry. It has an important role in reducing vulnerability, increasing resilience of farming systems and buffering households against climate related risks in addition to providing livelihood security. However, with so much contribution and potential, the agroforestry on account of its dependency on multi-institutions and multi-disciplinary approach, has not gained momentum in a significant way. Agroforestry growth and development is influenced by a number of policies. State regulations and permit systems for felling of trees and for timber transportation have been main interferences in marketing of timber grown on farmers’ land by private investment and have been major discouragement to the expansion of agroforestry. The article advocates strongly for an urgent action to initiate National Agroforestry Policy and launching of a National Mission on Agroforestry for its promotion in the country. It also highlights the efforts and initiatives taken in this regard and the ongoing efforts in this direction.